Effect of sport training on forearm bone sites in female handball and soccer players - Boshnjaku, A.; Dimauro, I.; Krasniqi, E.; Grazioli, E.; Tschan, H.; Migliaccio, S.; Di Luigi, L.; Caporossi, D. (The Journal of Sports Medicine and Physical Fitness, 2016)
Background: The objective of this study was to evaluate the bone mineral density (BMD) and Z-score of a skeletal region, considered as weight-bearing site in trained handball players (HP), but as non-weight-bearing site in trained soccer players (SP). The bone health status of the same site was also analyzed in an untrained group (CG).